Association of seventeen definitions of remission with functional status in a large clinical practice cohort of patients with rheumatoid arthritis - Carvalho, Danilo O.; O. Ferreira, Ricardo J.; Landewé, Robert; Vega Morales, David; Salomon Escoto, Karen; Veale, Douglas J.; Chopra, Arvind; Da Silva, José A. P; Machado, Pedro M. (The Journal of Rheumatology Publishing Company, 2020)
Objective: To compare the association between different remission criteria and physical function in rheumatoid arthritis patients followed in clinical practice. Methods: Longitudinal data from the METEOR database were used. Seventeen definitions of remission were tested: ACR/EULAR Boolean-based; Simplified/Clinical Disease Activity Index (SDAI/CDAI); and fourteen Disease Activity Score (DAS)-based definitions. Health Assessment Questionnaire (HAQ)≤0.5 was defined as good functional status. Associations were investigated using generalised estimating equations (GEE). Potential confounders were tested and sensitivity analyses performed. Results: Data from 32,915 patients (157,899 visits) were available. The most stringent definition of remission was the ACR/EULAR Boolean-based definition (1.9%). The proportion of patients with HAQ≤0.5 was higher for the most stringent definitions, although it never reached 100%. However, this also meant that, for the most stringent criteria, many patients in non-remission had HAQ≤0.5. All remission definitions were associated with better function, with the strongest degree of association observed for the SDAI (adjusted OR (95% CI): 3.36 (3.01-3.74)). However, only minor differences were noted between definitions (range of adjusted OR 1.99 to 3.36). Sensitivity analyses yield similar results. Conclusions: The seventeen definitions of remission confirmed their validity against physical function in a large international clinical practice setting. Achievement of remission, according to any of the indices may be more important than the use of a specific index. A multidimensional approach, targeted at wider goals than disease control, is necessary to help all patients achieve the best possible functional status.